DETERMINATION OF CRITICAL POINT OF CHICKEN FILLET DAMAGE USING POLYETHYLENE PACKAGING AT 4°C STORAGE TEMPERATURE - Rosalina Ilmi AMALIA; Bunayya Rabbika FIRLY; Bella Alfiah SIMAMORA; Nurul SAKINAH; Tita RIALITA; Gemilang Lara UTAMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The use of plastic for packaging fillet chicken meat is known to not significantly inhibit the growth of microbial contaminants. One alternative solution to maintain the freshness of fillet chicken meat at low temperature storage (± 4OC) is to use active packaging based on natural ingredients with the addition of antimicrobials. Based on this, the determination of the critical point of damage to fillet chicken meat during storage is important to know as a basis for comparison to determine the effectiveness of packaging applications in extending the shelf life of fresh chicken meat. This study aims to determine the critical point of damage to fillet chicken meat which is packaged using polyethylene (PE) type plastic and stored at a storage temperature of ± 4 °C. The study was conducted using descriptive methods, where fillet chicken meat was stored until characteristics are not favoured by panellists. Observation parameters consisted of acidity (pH), total number of microbial plate counts (TPC), colour change (∆E), texture (elasticity), presence of Salmonella, Shigella, and Escherichia coli contamination, and the preference level test for colour, aroma and texture of chicken fillet. The results showed a critical point of damage to fillet chicken meat occurred on the 3rd day marked by a decrease in quality during storage, namely an increase in pH due to decomposition, an increase in the total number of microbes by 2 logs since the first day of storage, lightness on the meat was getting darker, and decreasing the value of the consistency of chicken fillet. Detection of Salmonella, Shigella, and E.coli bacterial contamination was negative on the first day, but was detected positive on the 3rd day. Panellists began rejecting fillet chicken meat on the 3rd day of storage based on the parameters of colour, aroma and texture of chicken meat.